HealthyGirl kitchen : 100+ plant-based recipes to live your healthiest life - Brown, Danielle (Internet personality) (DK Publishing, 2023)
"An accessible plant-based cookbook from a non-judgmental vegan featuring delicious and easy recipes that will make you feel your best! Whether you're a practicing vegan or just interested in trying out more plant-based meals, HealthyGirl Kitchen is the go-to cookbook for insanely easy, out-of-this-world delicious recipes that will help you become the best version of yourself. Danielle Brown is the wildly popular vegan influencer behind HealthyGirl Kitchen, having created hundreds of recipes that are simple and approachable. These recipes will show you how to make nourishing meals that are free of animal products without making you feel like you're restricting yourself or missing out. Transitioning to a plant-based lifestyle can seem intimidating, but when you're in the HealthyGirl Kitchen, plant-based eating doesn't have to be complicated. Danielle covers the entire food-prep spectrum...The HealthyGirl Kitchen cookbook contains over 100 plant-based recipes that are 100% vegan, refined-sugar and flour free, gluten-free optional, and ridiculously easy to prepare. Pretty soon you'll be savoring these fresh meals and telling your healthy besties all about it."--provided by publisher.